Long-term exposure to elevated in a natural Quercus ilex L. community: net photosynthesis and photochemical efficiency of PSII at different levels of water stress - Scarascia-Mugnozza, G (Plant, Cell & Environment, 1996)
Naturally grown trees of Mediterranean evergreen oak (Quercus ilex L.), representing tbe climax species of tbe region, were enclosed in six large open-top chambers and exposed to ambient and elevated CO2 concentrations during a 3 year period. Maximum daily net photosynthetic rates measured at the two different CO2 concentrations were from 30 to 100% higher in elevated than in ambient [CO2] throughout the experimental period. The increase in maximum daily photosynthesis was also accompanied by a 93% rise in the apparent quantum yield of CO2 assimilation, measured during periods of optimum soil moisture conditions. Hence, no clear evidence of downregulation of net photosynthetic activity was found. Interactions between atmospheric CO2 concentration and plant water stress were studied by following the natural evolution of drought in different seasons and years. At each level of water stress, the maximum rate of carbon assimilation was higher in elevated than in ambient [CO2I by up to 100%. Analysis of in vivo chlorophyll fluorescence parameters in normal (21%) and low (2%) oxygen concentrations provided useful insights into the functioning and stability of the photosynthetic processes. The photochemical efficiency of PSII (Fy/F„,) progressively decreased as drought conditions became more evident; this trend was accentuated under elevated tCO2]. Thermal de-excitation processes were possibly more significant under elevated than Under ambient [CO2], in a combination of environmental stresses. This research suggests two possible conclusions: (i) a 'positive' interaction between elevated [CO2] and carbon metabolism can be obtained through relief of water stress limitation in the summer months, and (ii) elevated [CO2], under drought conditions, may also enhance the significance of slow-relaxing quenching.
Keywords: chlotophyll fluorescenee; elevated [CO2]; Mediterranean ecosystems; photosynthesis; Quercus ilex L.; water stress